The Effect of Project-Based Learning Model on Creativity and Learning Outcomes of Basic Electrical Engineering - Mustafa, Andreas; Olii, Djami; Sangi, Nontje (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2024)
This study aims to determine the effect of project-based learning models on creativity and learning outcomes of Electrical Installation and Power Engineering students in the Basic Electrical Engineering subject in class XI of SMKN 1 Airmadidi. This study used an experimental method with a post-test-only control group design. The instruments used included learning outcome tests and creativity questionnaires. The results showed a significant difference in the learning outcomes of Basic Electrical Engineering between students who were involved in learning using project-based models and those who followed conventional methods. This indicates that applying project-based learning models substantially affects the learning outcomes of Basic Electrical Engineering in Class XI of SMKN 1 Airmadidi with a ttable value < tcount or 4.10 < 6.773. The project-based model also shows the level of creativity between students who undergo learning with a project-based approach and those who use conventional methods. These findings indicate a significant effect of the project-based learning model on student learning creativity in Class XI of SMKN 1 Airmadidi with a ttable value < tcount or 4.10 < 6.418.